The Effect of Tax Collection, Tax Audit, and Taxpayer Compliance on Corporate Income Tax Revenue at The Tax Service Office Pratama Pancoran - W., Wenty Wandira; Utaminingtyas, Tri Hesti; Fauzi, Achmad (Nexus Synergy: A Business Perspective, 2023)
This study aims to determine the effect of tax collection, tax Audit, and taxpayer compliance on corporate income tax at The Tax Service Office Pratama Pancoran. The techniques and methods in this study use a quantitative approach, that is using secondary data from data per month during 2017-2022. In the form of monthly corporate income tax revenue reports, monthly tax collection reports, monthly tax audit reports, and monthly corporate taxpayer compliance reports obtained from The Tax Service Office Pratama Pancoran. The data analysis technique used to test the hypothesis is regression analysis. The results of this research show that: (1) Tax collection has no influence on corporate income tax revenue. (2) Tax audit has influence on corporate income tax revenue. (3) Taxpayer compliance influence on corporate income tax revenue. The implications of this research will have an impact on decision making in policy making related to tax collection governance, tax audits, taxpayer compliance so that corporate income tax revenues can increase significantly and can be utilized for public benefit. In addition, the implications of this research can be used as a source of literature for other studies.